Postponement Of Elections Perspective Of Constitutional Law In The Indonesian Constitution - Alexander, Ongky; Okra, Rona (Hutanasyah : Jurnal Hukum Tata Negara, 2024)
Elections are a democratic party for the people as the holder of the highest sovereignty, namely electing members of the DPR, DPD, president, and vice president by the 1945 Constitution article 22E paragraph "general elections are carried out directly, publicly, freely, secretly, honestly and fairly every five once a year." However, due to recent issues saying that the 2024 election will be postponed, which was proposed by several political party leaders and one of President Joko Widodo's ministers for reasons of maintaining national economic stability, the author tries to divert research on the issue of postponing elections from maintaining financial stability to the realm of state administration and constitution. The author uses qualitative research methods because the data source and results of this research are from library research in the form of descriptions of words. In this research, secondary data sources are used where data sources include books, articles, and journals. Data collection techniques are generally carried out by looking for data sources so that this research is carried out only based on written works, including research results that have been published, and that still need to be published. With the discussions and the results of the research, the author can conclude that if the issue of postponing the election is implemented, then it is unconstitutional or a violation of the Indonesian constitution and state administration; if this discourse is implemented by the government unilaterally without considering the will and opinion of the people.